Pentingnya Pengadaan Program Kerja “Cara Memanajemen Keuangan dengan Menggunakan Metode Menabung” Bagi Siswa/I SD dalam Program Kampus Mengajar: Procurement of Work Programs Importance "How to Manage Finance Using the Saving Method” for Elementary School Students in The Teaching Campus Program - Situmorang, Mariani; Deliana Rambe; Lorens Simorangkir (SENTIMAS: Seminar Nasional Penelitian dan Pengabdian Masyarakat, 2022)
The introduction of management to the child is very useful, especially honing the child’s ability to manage the money he has. Managing finances in a sense, the child is able to manage the money he has and is smart in dividing it, how much it will be used to buy necessities and still set aside a little money to save. With the introduction of the program to direct practice, children will naturally consider this habit to be an obligation for them, so that they will be helped in the future. In addition, saving from an early age also creates a positive child’s personality, trains patience, is able to appreciate money to be trained in children’s discipline in saving. In line with the existence of the Teaching Campus, which is one of the Merdeka Belajar Kampus Merdeka (MBKM) programs, each student team is required to have a work program that will be carried out during the assignment. This savings program is one of the best programs applied to children.